Ethnomedicinal breakthroughs in snake bite therapy: From folklore to forefront - Sana S. Hussain; Danie Kingsley, J (Toxicology Reports)
Snakebite envenomation is a critical public health issue, especially in tropical regions like India, resulting in significant morbidity and mortality. This review explores the potential of ethnomedicinal herbs as adjunct therapies to conventional antivenoms, addressing challenges such as the high cost, limited availability, and side effects of traditional antivenoms. The study emphasizes regional and species-specific variations in snake venom that complicate antivenom development and highlights the pharmacological potential of certain medicinal plants in mitigating venom effects. These plants offer an affordable, accessible alternative, though their efficacy can vary due to regional venom differences. Additionally, the review discusses the role of bioinformatics in advancing antivenom research, aiming to combine traditional knowledge with modern science to develop effective and accessible snakebite treatments in resource-limited settings.